Foundation years and why they matter - Leech, Stephen; Hale, Sarah (Emerald Publishing Limited, 2024)
Every year, thousands of British students enter higher education via a foundation year. Despite their growing popularity, the place of foundation years has become an increasingly contested issue: little is actually known about them outside the sector and they are widely misunderstood, leading some to question their value. As this book demonstrates, though, foundation years are not homogeneous - they are diverse products of the institutions, students and communities they serve, providing vital pathways into higher education that address the specific needs of underrepresented and disadvantaged groups studying at specific universities, widening access and promoting social mobility. Foundation Years and Why They Matter presents a selection of case studies, provided by experienced foundation year practitioners from twelve different UK Universities, illustrating the diversity of foundation year provision and delivering a compelling narrative about what foundation years are, what they do, how they do it, and the impact they have. This new and unique contribution to the literature on higher education and widening access is designed to help politicians, policy makers, and educators better understand UK foundation years and why they matter to the sector, to institutions, and above all to students.
Includes index.
Keywords: Education, Higher -- Great Britain.; Education -- Educational Policy & Reform -- General.; Higher education, tertiary education.; Educational strategies and policy.; elektronické knihy; electronic books